Effect of Fiber Morphology and Elemental Composition of Ananas comosus Leaf on Cellulose Content and Permittivity - Nurhafizah, Abu Talip Yusof; Norazwina, Zainol; Nor Hazwani, Aziz; Mohamad Shaiful, Abdul Karim (King Mongkut's Institute of Technology Ladkrabang, 2023)
The fiber morphology and elemental composition of pineapple leaf fibers were analyzed to understand their effect on the cellulose content and permittivity value. Cellulose fiber was extracted from pineapple leaf via the alkaline treatment method, and the content was determined using the Kurschner-Hanack method. The permittivity value of the developed cellulose fiber was measured based on the waveguide technique in the G-band. The surface morphology of the developed fiber was examined with scanning electron microscopy. Meanwhile, energy dispersive X-ray (EDX) spectroscopy was used to identify the elemental composition of the pineapple leaf fibers. The findings were that the cellulose fibers with the least diameter and distance between fibers exhibited the highest permittivity value, which was 1.85. The EDX analysis demonstrated that carbon was the commonest elemental in all fibers, and was 55 wt.% of the total element composition. Furthermore, the results showed that the permittivity value increased as the carbon composition increased, and decreased as the oxygen composition increased. Hence, the morphological and elemental studies of the cellulose fiber are useful in determining the permittivity value of the cellulose fiber for material development. The high permittivity value of the pineapple leaf fibers is believed to have great potential for use in electronic components.